Fabrication and testing of composite corrugated-core sandwich cylinder. (1st March 2018) - Li, Wanxin; Sun, Fangfang; Wei, Weiyi; Liu, Debo; Zhang, Xi; Li, Ming; Fan, Hualin
Abstract: To get a strong, stiff and weight efficient cylindrical shell, carbon fiber reinforced corrugated-core sandwich cylinders (CSCs) were designed and made. The corrugated-core is made up of corrugated cylindrical shell and manufactured by mould hot pressing method. Split forming and integral filament winding forming methods were applied to make the CSC separately. Effects from non-wrapped and wrapped cylindrical ends were investigated individually. Uniaxial compression tests were performed to reveal the strength and failure mode. Split forming method makes the CSC stiffer but integral filament winding forming method makes the CSC stronger. With non-wrapped ends, the cylinders fail at end delamination and the load carrying capacity is 289.7 kN and 373.7 kN, respectively. The load is improved to 415.6 kN and 491.4 kN, respectively, when the cylinder is end-wrapped. Skin fracture controls the failure of the CSCs with wrapped ends and makes them stronger. Meanwhile, the load carrying ability of the CSC is stronger than lattice truss-core sandwich cylinders (LTSCs). Benefiting from the high axial load carrying ability of the CFRC corrugated shell, strength of the designed CSC failing at skin fracture improves at a magnitude of 50% compared with the referenced LTSC.